Metode Mentoring untuk Meningkatkan Kompetensi Guru dalam Pemantauan Karakter Siswa Berbasis Afeksi Selama PJJ - Fadiyah Suryani (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The aim of this research is to improve teacher competence in monitoring student character based on affection programs during Distance Learning (PJJ) by using the mentoring method. The subjects of this study were teachers of SMAN 5 Yogyakarta who got the assignment as homeroom teacher for class X, XI and XII. The research method used is school action research which is carried out in a cycle through four stages, namely; planning, implementation, observation, and reflection. Data collection was carried out through observation, interviews, questionnaires and documentation. Data analysis in this study was carried out by reflecting on the results of observations on the mentoring process of mentors to mentees. To give the meaning of the success of the action used criteria, namely the action is declared successful if after the action there is an increase in teacher competence in monitoring the character of students based on the affection program during the PJJ period reaches an average of at least 80 and the competence of the mentor in implementing mentoring monitoring of student character based on affection programs as long as PJJ reaches an average -a minimum of 90. The results of the analysis show that monitoring the character of students based on the affection program during PJJ by applying the mentoring method can improve teacher competence, namely the competence of teachers in monitoring the character of students in grades X, XI and XII by teachers in cycle I 67.1 and in cycle II amounting to 84,5, mentor competence in understanding mentoring methods in cycle I 86 and cycle II amounted to 92.5 with very good category.